2012
DOI: 10.1007/s11999-012-2448-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Children and Young Adults: A Late Effect After Chemotherapy for Bone Sarcoma

Abstract: Background Premature bone loss after childhood chemotherapy may be underestimated in patients with bone sarcoma. Methotrexate (MTX), a standard agent in osteosarcoma protocols, reportedly reduces bone mineral density (BMD). The literature, however, has reported cases of BMD reduction in patients with Ewing's sarcoma treated without MTX. Thus, it is unclear whether osteoporosis after chemotherapy relates to MTX or to other factors. Questions/purposes We therefore asked whether (1) young patients with a bone sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 34 publications
(55 reference statements)
3
46
1
Order By: Relevance
“…Most of the existing literature data on bone mineral density in bone sarcoma patients focused on adults and reported reduced BMD values and high prevalence of osteoporosis in long-term survivors [3,15,17]. Similar to us, decreases in total and regional BMDs in young adults with bone sarcomas after anti-cancer therapy were observed by Holzer et al [4], Ruza et al [5], and PirkerFruhauf et al [12].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Most of the existing literature data on bone mineral density in bone sarcoma patients focused on adults and reported reduced BMD values and high prevalence of osteoporosis in long-term survivors [3,15,17]. Similar to us, decreases in total and regional BMDs in young adults with bone sarcomas after anti-cancer therapy were observed by Holzer et al [4], Ruza et al [5], and PirkerFruhauf et al [12].…”
Section: Discussionsupporting
confidence: 65%
“…In another study, lower levels of bone formation markers (carboxyterminal propeptide procollagen type I -PICP, OC) and increased (in about 20%) resorption marker (carboxyterminal cross-linked telopeptide of type I collagen -ICTP) in bone cancer survivors were found [5]. Pirker-Fruhauf et al [12] showed increased PICP, BALP, OC, CTX, TRAP (tartrate-resistant acid phosphatase) levels, and decreased RANKL concentration in some patients with bone cancers. However, these differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…During the period of bone accumulation in childhood and adolescence, a malignant tumor and its treatment can affect bone turnover and decrease bone mineral density (BMD) [18]. Reduced levels of BMD were reported in long-term survivors of childhood cancers, such as leukemia [2,17], osteosarcoma [18], and a few mixed solid pediatric tumor cohorts [3,26,30,32,34]. Therefore, in survivors of Ewing tumors, an accumulation of treatment-induced effects may compromise bone [3,25].…”
Section: Introductionmentioning
confidence: 99%